Integration of Kaili Cultural Values in the Development of Learning Resources in Elementary School: A Naturalistic Qualitative Approach - Herlina, Herlina; Amiruddin, Ayu Cahyani; Firmansyah, Arif; Surahman, Surahman; Vivekanantharasa, Raveenthiran; Rasli, Amran (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
The advancement of information and communication technology has brought major changes in the world of education, including the use of learning resources. However, globalization also has the potential to distance students from local cultural values. This study aims to explore the development of learning resources based on Kaili local culture in learning in grade IV of Elementary School using naturalistic qualitative methods. Data were collected through observation, in-depth interviews, and documentation studies with research subjects consisting of teachers, students, principals, and cultural figures at elementary school Sunju. The results of the study indicate that the learning resources used still do not accommodate local culture, while students are more familiar with foreign cultures than Kaili culture. Teachers have difficulty integrating local culture due to limited teaching materials. The principal supports the development of learning resources based on local culture, but training is needed for teachers so that its implementation is more effective. These findings indicate that the development of learning resources based on local culture can enrich students' learning experiences and strengthen their cultural identity, although it still faces challenges in implementation. This study emphasizes the importance of the role of education in preserving local culture through the development of relevant and contextual learning resources.